The Association of Immune Infiltrate of Primary Luminal B-Like Breast Cancer with Age - Hussain Farooq, Madiha Ehsan-Ul-Haq, Rafiq Ahmed Shahid, Attia Lateef, Usman Nasir, Sameen Hassan, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The effect of aging on immune response of luminal breast cancer is not effectively characterized leading to lack of substantial data which can be generated from age associated dynamics of immunity in luminal B cells. Objective: To assess the association of immune infiltrate of primary luminal B like breast cancer with age. Study Design: Prospective study. Place and Duration of Study: Department of Pathology, Sharif Medical & Dental College, Lahore from 1st April 2019 to 31st October 2023. Methodology: Seventy breast carcinoma patients were enrolled. The patients were diagnosed with grade I, II or grade III invasive breast carcinoma (identified through core needle biopsy) and had upfront surgery. The patient included in the study has clinical tumor size of ≥1.5 cm, receptor-status HR+/HER2-, and were within the age group of 25-70 years. Those patients who were between 35-50 years were categorized as younger patients while those between 51-65 years were categorized as middle patients and those above 65 years were old patients. To characterize the immunogenic tumor immune microenvironment (TIME) the tissue microarrays (TMA) were made by applying the Gran master for TMA. An overall three tissue microarrays were formulated which contained 250 tissues from 70 patients. These were used for orientation within tissue microarrays during multiple labeling by antibody neo deposition (MILAN) workflow. Staining and scanning of TMA slides was performed. Overall methodology included tissue dissection as well as analytical cell composition, functional and spatial analysis. Results: Majority within the age of 66-70 years followed by 51-65 years. The deserted tumor pattern was highest in elderly patients. The histological subtypes present invasive breast carcinoma-no special subtype (IBC NST) in all the breast carcinoma cases within the age group of 35-50 years. The tumor grading showed that majority of the breast carcinoma patients had grade II tumor with 53.3% seen in younger age while 60% of the breast carcinoma patients each from middle and older age also presented grade II tumor. The grade III tumor was observed in 46.6%, 40% and 34.28% breast carcinoma cases young to adult respectively. The nodal status presented with pNO cases at highest frequency. The B cell infiltration observed in the invasive front (IF) and tumor centre (TC) were significantly increased in the inflamed tumor than in desert tumors. The cell fraction presented increased number of T cytotoxic (Tcy), as well as T follicular helper (Tfh) cells in inflamed tumors while compared with deserted tumors in TC and IF. In the old age category it was observed that there was consistent negative correlation of OX-40+ Tcy cells with percentage. Conclusion: Aging is related to the immune profile alterations at cellular level inside the microenvironment of luminal B-like breast carcinoma tumor cells. The expression of OX-40 has no association with age signifying persisted capacity of inducing an anti-tumor immune-response. Keywords: Association, Immune infiltrate, Luminal B like breast cancer